Answer:
![z=-(5xy)/(96)](https://img.qammunity.org/2023/formulas/mathematics/college/juuxm78za05dxjjy8r0yu2clbpo3n6yy93.png)
Step-by-step explanation:
We're told that z varies jointly with the product of x and y. This can be represented as;
![\begin{gathered} z\propto xy \\ z=\text{kxy} \\ k=(z)/(xy) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w9bdz7a47w0c2j80f227p6aq5czdca7xdi.png)
We're also given the below values;
x = -4, y = 3, and z = 5/8
Let's go ahead and substitute these values into our equation and solve for k;
![k=((5)/(8))/(-4*3)=((5)/(8))/(-12)=(5)/(8)*(-(1)/(12))=-(5)/(96)](https://img.qammunity.org/2023/formulas/mathematics/college/5pby0hs72mutjlspo3b93gjul9bz1chzp2.png)
Since k = -5/96, the equation can now be written as;
![z=-(5xy)/(96)](https://img.qammunity.org/2023/formulas/mathematics/college/juuxm78za05dxjjy8r0yu2clbpo3n6yy93.png)